IMPLEMENTASI KEADILAN RESTORATIF DALAM PENYELESAIAN PERKARA PIDANA ANAK : STUDI PADA PENGADILAN TINGGI TANJUNG KARANG - Fitri Dwiarti (Fakultas Hukum Universitas Tulang Bawang, 2020)
The purpose of this research to determine and analyze the extent to which restorative justice is implemented in the settlement of juvenile criminal cases at the Tanjung Karang High Court and to determine the inhibiting factors for law enforcers to implement restorative justice in resolving juvenile criminal cases at the Tanjung Karang High Court. This research is an empirical juridical legal research. Based on the research results, the application of restorative justice at the Tanjung Karang High Court has been carried out although it is not optimal. The application of restorative justice to children in conflict with the law in resolving child criminal cases at the Tanjung Karang High Court is still experiencing obstacles. These obstacles include the limping of the substance of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, the short duration of case handling, and the minimum budget.